2015
DOI: 10.1080/14783363.2015.1044892
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and practices in Halal meat preparation: a case study investigation of a UK slaughterhouse

Abstract: Consumer concerns over the provenance of food that has been prepared in accordance with religious requirements has risen in importance. Instances of improper identification and sale of Halal meat-based products in particular have given rise to questions over the authenticity of such foods. Despite this and the rising demand for Halal foods across the globe, little research has been conducted around the specific issues that arise during their production. This paper presents a case study investigation of a slaug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…In other words, non-Muslim respondents believe halal has unquestionable sources in term of its safety. Many studies on halal have provided considerable evidence that halal products are safe and have been certified as safe, hygienic and healthy (Elseidi, 2017;Rezai et al, 2012;Thomas et al, 2017). However, there are some distinct misconceptions worthy of mention.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, non-Muslim respondents believe halal has unquestionable sources in term of its safety. Many studies on halal have provided considerable evidence that halal products are safe and have been certified as safe, hygienic and healthy (Elseidi, 2017;Rezai et al, 2012;Thomas et al, 2017). However, there are some distinct misconceptions worthy of mention.…”
Section: Discussionmentioning
confidence: 99%
“…Some faiths prescribe the foods that may be consumed by their followers and the methods by which those foods are produced (Thomas et al, 2017). Perhaps the most commonly known ritualised methods of food production and preparation are those of Islam (Halal) and Judaism (Kosher), but even these are not well understood by food manufacturers (Regenstein, Chaudry, & Regenstein, 2006).…”
Section: Faith-based Food Production and Preparationmentioning
confidence: 99%
“…Evidence shows that the methods of provisioning faith‐based foods, and their consequent acceptability to consumers, are intrinsically linked yet highly complicated systems (White & Samuel, ). Significant deficiencies in the methods of Halal food production, for example, have been found that include loss of traceability, cross‐contamination, and the misidentification of Halal and non‐Halal slaughtered meat products (Thomas et al ). Issues such as these have led to large‐scale changes in food production policy and practice around the world as methods of ritualised slaughter in particular have come under increased scrutiny (BBC, ; RSPCA, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The media, for example, report instances when pork DNA had been found in Halal food thereby rendering it Haram (not permissible) (BBC 2013a(BBC , 2013b and occasions when non-Muslims have been provided with Halal food without their knowledge or consent (Penman 2010;Taher 2010). Recent research has also identified significant operational deficiencies in slaughterhouses that undermine the authenticity of Halal food (Thomas et al 2015).…”
Section: Introductionmentioning
confidence: 99%